2013
DOI: 10.4236/ijcm.2013.41001
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Toxoplasmosis: A Case Report

Abstract: Report a case of a male patient with a macular scar compatible with ocular toxoplasmosis (OT) in right eye (RE) and review the relevant literature on this disease. A patient, who attended for a routine contact lens follow up, presented with amblyopic exotropia without any ocular disease. Best-corrected visual acuity of the affected eye was 20/40 with constant and mono-fixation exotropia. Ophthalmoscopic assessment revealed a macular scar compatible with OT. OT is the leading cause of infection in the posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…A recurring episode is possible, particularly if the patient's immune system is impaired. Some studies have reported the incidence of recurrences being common between the first and third decade of life (16)(17)(18)(19). The findings in this case are consistent with these aforementioned studies (16)(17)(18)(19), as the patient, who was also in her third decade of life, presented with a chorioretinal scar and adjacent retinitis suggesting the recurrence of active disease.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A recurring episode is possible, particularly if the patient's immune system is impaired. Some studies have reported the incidence of recurrences being common between the first and third decade of life (16)(17)(18)(19). The findings in this case are consistent with these aforementioned studies (16)(17)(18)(19), as the patient, who was also in her third decade of life, presented with a chorioretinal scar and adjacent retinitis suggesting the recurrence of active disease.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have reported the incidence of recurrences being common between the first and third decade of life (16)(17)(18)(19). The findings in this case are consistent with these aforementioned studies (16)(17)(18)(19), as the patient, who was also in her third decade of life, presented with a chorioretinal scar and adjacent retinitis suggesting the recurrence of active disease. This is also supported by the serology of raised IgG titres but with normal IgM titres, which suggests a previous infection rather than a recent infection.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When women acquire the infection more than 6 months prior to gestation, risk of transmission to the fetus is considerably reduced. Although preventable and treatable, congenital, ocular, and postnatal T. gondii infection is not curable and persists in all infected persons (Ortiz et al 2013; Peyron et al 2016; Ngo et al 2017). Latent or primary toxoplasmosis can be particularly dangerous in individuals with compromised immune systems, including those treated with corticosteroids, cytotoxic medicines, and antibody to tumor necrosis factor alpha (Lykins et al 2016; Wang et al 2017).…”
Section: Natural History Of Toxoplasma Gondiimentioning
confidence: 99%